Quality of antibody responses by adults and young children to 13-valent pneumococcal conjugate vaccination and Streptococcus pneumoniae colonisation. Issue 50 (28th November 2022) - Wolf, Asia-Sophia; Mitsi, Elena; Jones, Scott; Jochems, Simon P.; Roalfe, Lucy; Thindwa, Deus; Meiring, James E.; Msefula, Jacquline; Bonomali, Farouck; Makhaza Jere, Tikhala; Mbewe, Maurice; Collins, Andrea M.; et al.
Abstract: Childhood pneumococcal conjugate vaccine (PCV) protects against invasive pneumococcal disease caused by vaccine-serotype (VT) Streptococcus pneumoniae by generating opsonophagocytic anti-capsular antibodies, but how vaccination protects against and reduces VT carriage is less well understood. Using serological samples from PCV-vaccinated Malawian individuals and a UK human challenge model, we explored whether antibody quality (IgG subclass, opsonophagocytic killing, and avidity) is associated with protection from carriage. Following experimental challenge of adults with S. pneumoniae serotype 6B, 3/21 PCV13-vaccinees were colonised with pneumococcus compared to 12/24 hepatitis A-vaccinated controls; PCV13-vaccination induced serotype-specific IgG, IgG1, and IgG2, and strong opsonophagocytic responses. However, there was no clear relationship between antibody quality and protection from carriage or carriage intensity after vaccination. Similarly, among PCV13-vaccinated Malawian infants there was no relationship between serotype-specific antibody titre or quality and carriage through exposure to circulating serotypes. Although opsonophagocytic responses were low in infants, antibody titre and avidity to circulating serotypes 19F and 6A were maintained or increased with age. These data suggest a complex relationship between antibody-mediated immunity and pneumococcal carriage, and that PCV13-driven antibody quality may mature with age and exposure. Highlights: PCV13 reduces colonisation after experimental S. pneumoniae challenge in adults. Vaccinated adults had strong serotype-specific functional antibody responses. Unvaccinated adults with high avidity antibodies were less likely to be colonised. Residual carriage of vaccine serotypes maintains IgG titres in vaccinated children. Vaccinated children maintain serotype-specific avidity without antigen re-exposure.